Eco-Brick Innovation: An Educational Approach to Plastic Waste Management - Veronika Nugraheni Sri Lestari; Luluk Indarinul Mufidah (STAI Miftahul ULa Nganjuk, 2025)
This community service initiative addresses the critical issue of plastic waste through an Asset-Based Community Development (ABCD) approach, implemented at SDN Senggowar 01 in Senggowar Village. The program focuses on transforming non-productive assets specifically, used plastic bottles into productive and valuable resources in the form of eco bricks. By leveraging the school as an educational hub, the project engaged students in hands-on activities that combined environmental education with practical skills development. The process included collecting plastic waste, processing it into eco bricks, and utilizing these bricks to create functional items such as shoe racks and waste bins. This initiative not only provided a tangible solution to plastic waste management but also fostered environmental awareness and creativity among students. The ABCD framework ensured that local assets were maximized, community participation was enhanced, and sustainable practices were introduced, resulting in meaningful social change and a cleaner school environment